Global competence of employees in hispanic enterprises on the U.S./Mexico border = Competencias Globales de los Empleados en las Empresas Hispanas de la Frontera Estados Unidos/México - Blanco Jiménez, Mónica; Rositas Martínez, Juan; Jardines Garza, Francisco Javier
Abstract: Developing interculturally competent students who can compete successfully in the global market is one of the challenges for institutions of higher education. A common assumption is that the processes by which people are educated need to be broadly consistent with the way in which organizations operate in a globalizing environment, especially enterprises along the border of the United States and Mexico. The geographical proximity of these countries creates a global dynamic between the two cultures requiring international staff. With this in mind, we turned to managers of Hispanic-owned business to report whether they believed, their employees possess the competences (knowledge, skills, attitudes, and experiences) deemed necessary for attaining global competency. We developed a questionnaire created by Hunter (2004) to measure global competencies. In our results we found that employees of the Hispanic enterprises that were targeted do not generally have a high level of global competence according to our indicators.